DEFINITION OF INVESTMENT STRATEGY FOR SUSTAINABLE DEVELOPMENT OF REGIONAL ECONOMIES - Ahmedov Oybek Turgunpulatovich; Nurqulov Nurbek Sirojiddin o’g’li (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article is discussed that the theoretical foundations of determining the investment strategy for sustainable development of the region’s economy, as well as the current situation, analysis and future plans.